2017
DOI: 10.1108/stics-09-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

The future of telephone surveys in Hong Kong

Abstract: Purpose This paper aims to compare residential fixed-line telephone surveys with cell phone surveys for assessing the extent of the potential undercoverage issue evaluating the necessity and feasibility of conducting cell phone surveys or dual-frame telephone surveys in Hong Kong. Design/methodology/approach The research team simultaneously carried out a conventional fixed-line telephone survey and a cell phone survey in 2015 with similar features on survey design, sampling and data collection procedures. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Perceived sufficiency and quality of family communication partially mediated the association of PSU with family well-being. We observed that the mobile sample included more young, highly educated, unmarried, employed, and high-income respondents, which was consistent with the findings of another study comparing two sampling frames in Hong Kong (Chiu & Jiang, 2017). The traditional random-digit-dialing landline survey may raise the undercoverage issue as the method cannot reach the increasing mobile-phone-only population (Chiu & Jiang, 2017;Keeter, Kennedy, Clark, Tompson, & Mokrzycki, 2007), which can be partially supported by our findings of more smartphone owners in the mobile sample than the landline sample (93.5% vs. 76.5%; p < .001).…”
Section: Discussionsupporting
confidence: 91%
“…Perceived sufficiency and quality of family communication partially mediated the association of PSU with family well-being. We observed that the mobile sample included more young, highly educated, unmarried, employed, and high-income respondents, which was consistent with the findings of another study comparing two sampling frames in Hong Kong (Chiu & Jiang, 2017). The traditional random-digit-dialing landline survey may raise the undercoverage issue as the method cannot reach the increasing mobile-phone-only population (Chiu & Jiang, 2017;Keeter, Kennedy, Clark, Tompson, & Mokrzycki, 2007), which can be partially supported by our findings of more smartphone owners in the mobile sample than the landline sample (93.5% vs. 76.5%; p < .001).…”
Section: Discussionsupporting
confidence: 91%
“…This low response rate might be due to the length of survey (about 1 hr) and participants' inclusive criteria (17-23 years old). Therefore, our response rate was lower than that (about 50%) of other Hong Kong telephone surveys targeting the general population (i.e., 18 years or older) [27]. Still, our study's response rate was closer to that of another study [33] using telephone survey in Hong Kong (17%) and within the range of response rates for telephone polling in the US [34].…”
Section: Resultsmentioning
confidence: 41%
“…The survey utilized a computer-assisted telephone interviewing (CATI) system for selecting local household telephone numbers. Chiu and Jiang [27] did a study comparing residential fixed-line telephone surveys with cell phone surveys to assess the extent of the potential undercoverage issue in Hong Kong. Results found that with increasing the number of mobile phone-only households, the household telephone survey was still a better representative of the Hong Kong population as most estimates from the telephone survey sample were very similar to the population statistics.…”
Section: Methodsmentioning
confidence: 99%
“…Third, a telephone survey was conducted to eliminate household contact during COVID-19. Although the dual-frame approach (landline and mobile) may result in sampling bias on demographic characteristics (Chiu & Jiang, 2017), the age and gender distributions of the present sample closely approximate those of the population census (Hong Kong Census and Statistics Department, 2022). Last, this cross-sectional survey precluded drawing conclusions about causality.…”
Section: Discussionmentioning
confidence: 74%